Scaling group consultations - the fourth healthcare revolution: A call to action to save primary care - Fraser Birrell; Denis Collen; Muir Gray (Wiley, 2023)
Abstract Compelling arguments support scaling of group consultations across the National Health Service (NHS) and globally. We need to recognise self‐care is the most important type of care for people with long‐term health problems. Healthcare systems like the NHS are essential for diagnosis, acute care and initiating optimal therapy but people are on their own over 99.95% of waking hours. We must accept and encourage the contribution that other people with the same long‐term health problems can make and enable both types of care through face‐to‐face and virtual group consultations.  Patients and communities need agency and choice to implement and access these patient‐centred and codesigned care models. This can bring system benefits, mapped to healthcare's quintuple aim, to those electing to use group consultations and even those who do not. The process of both training and delivering group consultation models can create and sustain compassionate communities and this 'Fourth Healthcare Revolution' may be exactly what is needed to save primary care.